Democratic Economic Enterprises - Esteves, A. (The Democratic Economy Initiative, 2021)
STRATEGIES OF RESOURCE MOBILIZATION TAMERA • Commercialization of knowledge; • International circle of donors and supporters. ESPERANÇA/ COOESPERANÇA • Philanthropical funds and technical knowledge mobilized through NGOs affiliated with the Catholic Church; • Public funds from state and na@onal-level policies. COOPERATIVA INTEGRAL CATALANA • “Economic disobedience”: Half a million Euros in bank loans, semi-squaJng of buildings; • Cybercurrency specula@on; • Quotas from members.